2019
DOI: 10.3390/s19173757
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Accuracy of Continuous Glucose Monitoring during Exercise through Physical Activity Tracking Integration

Abstract: Current Continuous Glucose Monitors (CGM) exhibit increased estimation error during periods of aerobic physical activity. The use of readily-available exercise monitoring devices opens new possibilities for accuracy enhancement during these periods. The viability of an array of physical activity signals provided by three different wearable devices was considered. Linear regression models were used in this work to evaluate the correction capabilities of each of the wearable signals and propose a model for CGM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…One of the cases presented a negative MARD value, which means that the MARD for exercise was lower (12.4%) than the pre-exercise value (16.8%). With respect to the resistance exercises, a greater accuracy of the sensors can be observed, as it was concluded in individual studies that compared resistance exercise and other exercises [ 8 , 46 ]. One of the cases also presented a negative MARD value, the MARD for exercise being 6.96% and the MARD for rest being 8.15%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the cases presented a negative MARD value, which means that the MARD for exercise was lower (12.4%) than the pre-exercise value (16.8%). With respect to the resistance exercises, a greater accuracy of the sensors can be observed, as it was concluded in individual studies that compared resistance exercise and other exercises [ 8 , 46 ]. One of the cases also presented a negative MARD value, the MARD for exercise being 6.96% and the MARD for rest being 8.15%.…”
Section: Discussionmentioning
confidence: 99%
“…Patients need to know that they can rely on CGM systems during any kind of situation with a fast and accurate response. Further work needs to be done exploring the impact of CGM accuracy on aerobic exercise, and possibly correcting that impact, as proposed by Laguna et al [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CGM systems may serve as a tool to reduce the risk of exercise-induced hypoglycemia. 30 Nevertheless, it has been shown that their accuracy drops during physical activity when compared to reference glucose measurements, 31 even so among the more recent devices, 32 likely because of the rapidly changing blood glucose concentrations. 33,34…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional studies are needed to better explore the performance of CGM systems under different exercise conditions (Forlenza et al, 2019). A better understanding of CGM accuracy under exercise conditions may provide evidence to develop CGM algorithms that may be able to compensate for mitigating its impact (Laguna Sanz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%